Sistema construtivo de rápida execução: anteprojeto de um terminal de ônibus urbano no bairro Planalto - Natal/RN - Borges, Andrecelly Solon (2021)
This Professional Master's Degree work consists of a preliminary project for an urban bus terminal for the Planalto neighborhood, with emphasis on a construction system of rapid execution, and a technical report. Currently, a large part of the population of Natal/RN uses urban bus public transport to carry out their daily activities, such as study, work and leisure. The public transport system of a city is not only abbreviated to vehicles that transport people along different routes, but also composed of buildings, their accesses and facilities, configuring itself as a protected and safe space. However, there is no equipment of this nature in Natal/RN, compatible with the demand of people who circulate daily through the city's bus terminals. Based on this need, the objective is to propose a preliminary project for a Planalto II Bus Terminal, in Bairro Planalto, which is functional and comfortable for the population. To develop the proposal, a theoretical-conceptual deepening on the theme was carried out, through bibliographical research and studies of related design references. Then followed the design phase, based on the definition of concept, starting with the architectural programming, definition of dilemmas and project goals. From this base and with the help of the curricular components of the course, the design process was gradually developed and mapped, through various forms of registration, from the initial stages of conditioning studies, conception, and development of the architectural party to the scope of the Terminal's proposal. As a result, there is a proposal for a functional building, using a tensioned roof, to be executed in a short period of time and with lower costs, when compared to other construction systems.